2020
DOI: 10.1016/j.eurox.2020.100108
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis-related biomarkers in women with endometriosis: The effects of dienogest and oral contraceptive therapy

Abstract: Objective Chronic inflammation in endometriosis is associated with increased risk of future cardiovascular disease; however, no studies have investigated the cardiovascular risk of women who have undergone hormonal therapy for endometriosis. We investigated atherosclerosis-related biomarkers in women with and without endometriosis and the effects of dienogest (DNG) and oral contraceptive (OC) therapies. Study design In this cross-sectional study, 109 women with endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…In the abovementioned study, Santoro et al failed to show a difference in carotid IMT, despite increased levels of several inflammatory markers and decreased FMD [22]. In a recent study, there was no difference in the mean CAVI when adjusted for age and ankle brachial index amongst groups [25]. On the contrary, Tani higher total cholesterol, LDL and triglycerides [7,27], whereas other studies found similar levels [19,21,22].…”
Section: Discussionmentioning
confidence: 88%
“…In the abovementioned study, Santoro et al failed to show a difference in carotid IMT, despite increased levels of several inflammatory markers and decreased FMD [22]. In a recent study, there was no difference in the mean CAVI when adjusted for age and ankle brachial index amongst groups [25]. On the contrary, Tani higher total cholesterol, LDL and triglycerides [7,27], whereas other studies found similar levels [19,21,22].…”
Section: Discussionmentioning
confidence: 88%
“…Maeda et al, 2020, found cIMT levels were significantly increased in women with endometriosis using oral contraceptives for an extended period. This is representative of arterial wall thickening, indicating an elevated risk for atherosclerosis [31]. As mentioned, the administration of hormonal therapy as part of a treatment plan for women with endometriosis for extended periods increases the risk of developing atherosclerosis and by extension cardiovascular disease due to the consequential increase in oxidative stress.…”
Section: Carotid Intima-media Thickness (Cimt)mentioning
confidence: 88%
“…For example, a 2020 study by Maeda et al investigated atherosclerosis-related biomarkers in women with endometriosis, where they used a VaSera VS-1000 vascular screen system. Using this equipment, they measure the SBP of the upper (brachial arterial) and lower (tibial arterial) SBP, dividing ankle SBP by brachial SBP to calculate the ABI index value [31]. It is often recommended that repeated measures of the ABI should be taken, preferably over an extended period prior to diagnosis.…”
Section: Ankle-brachial Index (Abi)mentioning
confidence: 99%
See 2 more Smart Citations